The effects of saffron supplementation on inflammatory factors and clinical outcomes in sepsis patients admitted to the intensive care unit (ICU): Study protocol for a double-blind randomized controlled clinical trial - Shirin Hassanizadeh; Babak Alikiaii; Mohammad Hossein Rouhani; Zeinab Mokhtari; Mohammadreza Moznebiisfahani; Manoj Sharma; Mohammad Bagherniya (Avicenna Journal of Phytomedicine)
Objective: Research studies have examined saffron's effects on inflammation, infection, and oxidative stress. Nevertheless, the effects of saffron on sepsis patients in the intensive care units (ICUs) have not yet been studied. Hence, this study will examine the effects of saffron supplementation on oxidative stress biomarkers, inflammation factors, and clinical outcomes in critically ill septic patients.Materials and Methods: Ninety patients with sepsis will participate in this parallel double-blind, randomized clinical controlled trial. In addition to usual care, the intervention group (n=45) will receive a daily tablet containing 100 mg/day saffron for 7 days, and the control group (n=45) will receive a placebo tablet containing 100 mg/day corn starch for the same duration. Acute Physiology and Chronic Health Evaluation II (APACHE II), the Sequential Organ Failure Assessment (SOFA), and the NUTRIC Score will be used to assess the patients' clinical and nutritional status at the beginning and end of the study. Inflammatory markers including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), and IL-18, indicators of oxidative stress including malondialdehyde (MDA), glutathione peroxidase (GPx), catalase, superoxide dismutases (SODs), and total antioxidant capacity (TAC), level of Glasgow Coma Scale (GCS), complete blood count (CBC), and lactate dehydrogenase (LDH) will be evaluated at beginning and end of the study. Twenty-eight days after the start of the intervention mortality rates will be assessed.Discussion: Due to the anti-inflammatory, antioxidant, and antimicrobial effects, saffron might have beneficial effects in critically ill patients with sepsis.